2021
DOI: 10.21009/jrpms.051.02
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Flipped Classroom Dalam Jaringan terhadap Kemampuan Pemecahan Masalah ditinjau dari Self Confidence Siswa Kelas X IPS SMA Negeri di Kecamatan Cempaka Putih Jakarta

Abstract: Kemampuan pemecahan masalah matematis merupakan suatu bagian utuh dari pembelajaran matematika karena pemecahan masalah merupakan suatu proses untuk mengatasi kesulitan yang ditemui supaya mencapai suatu tujuan yang diinginkan. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh model pembelajaran flipped classroom dalam jaringan terhadap kemampuan pemecahan masalah ditinjau dari self confidence siswa kelas X IPS SMA Negeri di Kecamatan Cempaka Putih Jakarta. Penelitian ini dilaksanakan di SMAN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The 2021 publication on online learning (Pinontoan et al, 2021) obtained positive effects of applying flipped classrooms with the support of e-modules on statistical learning on students' reasoning abilities and entrepreneurial intentions. As reported by Simanjuntak et al (2021), the effects of using flipped classrooms in online learning contribute to improvement of mathematical problem-solving skills, especially for students who have self-confidence and there is an interaction between the two. Hasanudin et al (2020) reported that the elaboration from flipped and google classroom generates asynchronous online learning syntax, which is capable of growing self-development, especially when students take part in Indonesian language learning, students are more skillful in using the four language skills, can write, and are self-awareness for their literacy.…”
Section: Introductionmentioning
confidence: 91%
“…The 2021 publication on online learning (Pinontoan et al, 2021) obtained positive effects of applying flipped classrooms with the support of e-modules on statistical learning on students' reasoning abilities and entrepreneurial intentions. As reported by Simanjuntak et al (2021), the effects of using flipped classrooms in online learning contribute to improvement of mathematical problem-solving skills, especially for students who have self-confidence and there is an interaction between the two. Hasanudin et al (2020) reported that the elaboration from flipped and google classroom generates asynchronous online learning syntax, which is capable of growing self-development, especially when students take part in Indonesian language learning, students are more skillful in using the four language skills, can write, and are self-awareness for their literacy.…”
Section: Introductionmentioning
confidence: 91%
“…A meta-analysis by Edy Nurtamam (2023) also concluded that the Flipped Classroom approach consistently improves the math achievement of elementary school students (Edy Nurtamam et al, 2023). In addition, Simanjuntak (2021) conducted a study that highlighted that Flipped Learning positively affects students' mathematics performance (Simanjuntak et al, 2021). A case study by Nurkhasanah (2021) shows that the application of Flipped Classroom can increase student engagement and their understanding of mathematical concepts (Nurkhasanah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to solve problems is one of the higher-order thinking skills needed by students in responding to the increasingly complex challenges of life in the future (Fajri, 2017;Irawati, 2018;Hidayati, 2017;Simanjuntak, Meiliasari, & Ambarwati, 2021). Tarhadi and Pujiastuti (2006), defines problem solving as a way of thinking, analyzing, and reasoning using experience and knowledge related to the problem.…”
Section: Introductionmentioning
confidence: 99%